Development of nanotechnology-mediated precision radiotherapy for anti-metastasis and radioprotection - Pan, Yuanbo; Tang, Wei; Fan, Wenpei; Zhang, Jianmin; Chen, Xiaoyuan (Chemical Society reviews, 2022)
Radiotherapy (RT), including external beam RT and internal radiation therapy, uses high-energy ionizing radiation to kill tumor cells. However, ionizing radiation inevitably damages the surrounding normal tissues. Therefore, it is imperative to develop precision RT for improving the treatment outcome and reducing the adverse effects. Recent breakthroughs in nanotechnology have provided a variety of strategies by which RT can precisely and efficiently eradicate local tumors. In this review, we would like to summarize a series of nanotechnology-mediated strategies to achieve precision RT, including tumor-targeted delivery, image-guided precision radiotherapy, and exo/endogenous stimuli-responsive nanomedicines for enhanced tumor accumulation/penetration. In addition, this review will also discuss two representative featured applications of precision RT: RT-induced immunotherapy against cancer metastasis and radioprotection of the surrounding healthy tissues. Since RT is usually thought to be only effective for treating local tumors, this review will interpret the unusual mechanisms of RT-mediated systemic antitumor immunity for eliminating distant cancer metastasis as well as the abscopal effects of RT in combination with other treatments (e.g., photodynamic therapy (PDT), chemodynamic therapy (CDT), etc.). Furthermore, this review will discuss nanotechnology-mediated radioprotection strategies for shielding healthy tissues from radiation damage. Finally, the current challenges and future prospects of precision RT are also elucidated with the intention to accelerate its clinical translation.Radiotherapy (RT), including external beam RT and internal radiation therapy, uses high-energy ionizing radiation to kill tumor cells. However, ionizing radiation inevitably damages the surrounding normal tissues. Therefore, it is imperative to develop precision RT for improving the treatment outcome and reducing the adverse effects. Recent breakthroughs in nanotechnology have provided a variety of strategies by which RT can precisely and efficiently eradicate local tumors. In this review, we would like to summarize a series of nanotechnology-mediated strategies to achieve precision RT, including tumor-targeted delivery, image-guided precision radiotherapy, and exo/endogenous stimuli-responsive nanomedicines for enhanced tumor accumulation/penetration. In addition, this review will also discuss two representative featured applications of precision RT: RT-induced immunotherapy against cancer metastasis and radioprotection of the surrounding healthy tissues. Since RT is usually thought to be only effective for treating local tumors, this review will interpret the unusual mechanisms of RT-mediated systemic antitumor immunity for eliminating distant cancer metastasis as well as the abscopal effects of RT in combination with other treatments (e.g., photodynamic therapy (PDT), chemodynamic therapy (CDT), etc.). Furthermore, this review will discuss nanotechnology-mediated radioprotection strategies for shielding healthy tissues from radiation damage. Finally, the current challenges and future prospects of precision RT are also elucidated with the intention to accelerate its clinical translation.